Oncological outcomes of colonic stents as “bridge to surgery” versus emergency surgery for obstructive colorectal cancer: A portuguese comparative study - Lourenço, L (2016)
Prémio Medtronic Investigação em Coloproctologia 2015, no XXV Congresso Nacional de Coloproctologia, que decorreu nos dias 26 e 27 de Novembro de 2015, no Porto.